Stand-alone ClpG disaggregase confers superior heat tolerance to bacteria - Lee, Changhan; Franke, Kamila B.; Bukau, Bernd; Mogk, Axel (Proceedings of the National Academy of Sciences of the United States of America, 2018)
AAA+ disaggregases solubilize aggregated proteins and confer heat tolerance to cells. Their disaggregation activities crucially depend on partner proteins, which target the AAA+ disaggregases to protein aggregates while concurrently stimulating their ATPase activities. Here, we report on two potent ClpG disaggregase homologs acquired through horizontal gene transfer by the species Pseudomonas aeruginosa and subsequently abundant P. aeruginosa clone C. ClpG exhibits high, stand-alone disaggregation potential without involving any partner cooperation. Specific molecular features, including high basal ATPase activity, a unique aggregate binding domain, and almost exclusive expression in stationary phase distinguish ClpG from other AAA+ disaggregases. Consequently, ClpG largely contributes to heat tolerance of P. aeruginosa primarily in stationary phase and boosts heat resistance 100-fold when expressed in Escherichia coli. This qualifies ClpG as a potential persistence and virulence factor in P. aeruginosa.
first published December 20, 2017
Gesehen am 25.02.2020